ER stress as a trigger of UPR and ER-phagy in cancer growth and spread - Cherubini, Alessandro; Zito, Ester (Frontiers in Oncology, 2022)
Tumors can survive environmental and metabolic stress by triggering homeostatic responses that re-establish the pre-stress status and permit them to grow and thrive. The endoplasmic reticulum (ER) is the organelle where proteins undergo post-translational modifications and are folded and exported to the secretory pathway. Its environment and activity are therefore fundamental for proteostasis, i.e., the plethora of mechanisms controlling protein formation, folding, degradation, and secretion, needed to assure protein balance and cellular health. In different tumor-related conditions, such as after the activation of oncogenes or under hypoxia and nutrient deprivation, the ER experiences stress, triggered by a high load of proteins to be folded compared to the limited folding capacity of the organelle. As a consequence, three ER membrane sensors and the related unfolded protein response (UPR) are activated. The UPR comprises a complex interconnection between signal transduction pathways that promote a homeostatic response that acts by increasing the amount of protein chaperones and of proteins involved in ER-associated protein degradation (ERAD) on one hand and attenuating protein translation on the other. ER-phagy, literally “eating” the ER, is part of another homeostatic response consisting of the clearance of non-functional ER portions including misfolded proteins. This response is also activated by a set of dedicated ER-phagy receptors after ER stimuli, which overlap the stimuli generating ER stress. Thus, the UPR and ER-phagy are two closely related homeostatic mechanisms that cooperate in re-establishing ER homeostasis. However, while the role of the UPR in favoring cancer growth and thriving by promoting angiogenesis, metastasis, chemotherapy resistance, and epithelial-to-mesenchymal transition is consolidated, that of ER-phagy is still in its infancy. This essay provides an overview of emerging concepts on ER stress, the UPR, and ER-phagy and their crosstalk in tumorigenesis. We also critically review new findings on their pharmacological targeting in cancer.